Pengaruh Peranan Pengguna Akhir, Prosedur, Data, Perangkat Keras dan Manajemen Proyek terhadap Keberhasilan Implementasi ERP: Studi Kasus PT Ciliandra Perkasa - Kurniawan, Roni (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Information technology improvement is one of drivers that changes in computer-based accounting information system called Enterprise Resource Planning (ERP) System. The advantages of ERP system leads companies decide to eventually implement the system. The objective of this study is to comprehend the impacts of some variables such as end-user role, procedure, data, hardware and project management to the success of ERP implementation, both partially and simultantly.This research implements descriptive analysis method where thedata are collected by questionare on a survey. Population is a company of oil-palm industry located in Pekanbaru - Riau which implements ERP system for its operational. Data are proccessed using SPSS version 17.00 and hypothesis testing is performed using statistic tests, which are validation test, reliability test and double regression test. The result and discussion of this study in general shows that end-user role, procedure, data, hardware and project management variables have positive correlation and influence to the success of ERP implementation, both partially and simultantly.